Out of the darkness - Rush, Jaime (Avon, 2009)
"Rand Brandenburg can see the future, yet thus far all he has done with his unique ability is become a skillful gambler. But according to the Offspring, his power has made him a target and could get him killed. So the loner used to living on the edge is now hiding out with others just like him, including Zoe Stoker, a mysterious redhead who has his heart soaring. But that's not the only thing Zoe's got flying. All her life, whenever she felt anything too intensely, objects would start moving. She's never been able to control her power, so instead she's shut down her emotions. Now, as a powerful enemy approaches, she's losing control of her heart. But letting love lead her out of the darkness might save her life"--Page 4 of cover.